Digital Technologies in Education 4.0. Does it Enhance the Effectiveness of Learning? A Systematic Literature Review - Qureshi, Muhammad Imran; Khan, Nohman; Raza, Hamad; Imran, Amina; ismail, Fadillah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Abstract— Over the past decade, digitalization shapes the overall educational structure worldwide, with the attention received from practitioners, researchers, and policymakers for educational development. Digital technologies are bringing massive changes across education, skills, and employment. These changes mirror how technology is increasingly central to education 4.0. Digital technologies are expanding beyond innovative and less traditional techniques of teaching and learning via education collaboration. However, the present study will explore the research conducted on digital technologies and education. Data is selected from the Scopus database reputed journals. The final 47 studies are chosen for the review process using PRISMA statement 2015, and bibliometric analysis is done to find the occurrence of keywords. The findings of the study are strengthening the value of educational growth and development of high-tech skills. Education’s Future focuses on digital technologies, and the traditional modes of education will be replaced entirely.